Silagens de Capim Tanzânia (Panicum maximum cv Tanzânia) em diferentes idades - Gustavo Henrique de Frias Castro (2008)
The aim of this study was to evaluate the potential for use of Tanzania grass (Panicum maximum cv. Tanzania) cut at different ages for the production of silage. In the first experiment, Tanzania grass, cut at 42, 63, 84, 107 and 126 days of growth, was evaluated considering its productivity, agronomic characteristics and chemical composition. It was observed gain in height of Tanzania grass until the 84th day, with increased production of green fodder and mass production of dry material with the advancing age of cutting of forage, with a decrease in the percentage of leaves and an increase in the percentage of stems. Regarding chemical composition, it was detected a decrease in crude protein percentage and an increase of fibrous fractions with the advancing of age. The results were reflected in the kinetics of rumen fermentation of Tanzania grass cut on the 42nd, 63rd, 84th, 107th and 126th days, described by semi-automated in vitro gas production technique, showing less potential for gas production, lower rate of fractional of fermentation, and consequently less effective degradability of dry matter. In the second experiment, the profile of fermentation of the Tanzania silage, cut on the 42nd, 63rd, 84th and 107th days of growth, at silo opening times of 0, 1, 3, 5, 7, 14, 28 and 56 days, was evaluated by using laboratory silos. According to the nutritional composition (dry matter, mineral matter, crude protein, neutral detergent fiber, acid detergent fiber, carbohydrates soluble in 80 % ethanol and in vitro dry matter digestibility) and to the parameters of fermentation (pH, ammonia nitrogen as a percentage of total nitrogen, lactic acid, acetic acid, propionic acid, butyric acid and ethanol), the Tanzania silage can be classified as a low quality one. In the third experiment it was studied the kinetics of degradation and fermentation of Tanzania silage cut on the 42nd, 63rd, 84th and 107th days, by using in situ and semi-automated in vitro gas production techniques. Concerning the in situ methodology, the values for effective degradability declined, as the age of cutting increased, for all nutritional fractions evaluated. For the parameters of kinetics of fermentation obtained by in vitro methodology, it was noticed that the the maximum potential for maximum gas production and effective degradability of dry matter in vitro declined as the age of cutting of ensiled forage increased. In the fourth experiment, it were evaluated the voluntary intake and apparent digestibility of nutritional components of Tanzania grass silage cut on the 42nd, 63rd, 84th and 107th days, whereas the values of metabolizable energy and net energy were determined through indirect calorimetry in silages of 63, 84 and 107 days. There was no difference noticed in the voluntary intake of dry matter, neutral detergent fiber and acid detergent fiber of grass silage in sheep. The voluntary intake of crude protein decreased as the age of cutting of ensiled forage increased, until the age of 84 days. The concentrations of total digestible nutrients have also decreased as the age of cutting of forage increased. It was not observed a significant difference to the efficiency of use of metabolizable energy for maintenance among different silages. For the production of grass silage, Tanzania should not be cut in the range of 42 to 63 days.